METODE STRUKTURAL ANALITIK SINTETIK (SAS) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA HURUF BRAILLE PADA ANAK TUNANETRA DI BHAKTI LUHUR MALANG - Klemensi Nini; Regina Harum (Jurnal Pelayanan Pastoral, 2023)
This research was motivated by the difficulty in reading braille in blind students shown by non-fluent behavior in reading both syllables, words and simple sentences in braille. In addition, subjects were slow to identify syllables, and hesitated in reading, especially when reading simple readings, consisting of 3-5 sentences. The purpose of this study was to determine whether the Structure Analysis Synthesis (SAS) method can improve braille reading skills in blind children in Bhakti Luhur Malang who are in grade  II SDLB-A. The method used is an experimental method with a Single Subject Research design A-B-A design. The results showed that in the baseline phase (A1) which was carried out as many as 3 sessions, the average score was 44.3%. Meanwhile, in the Intervention phase (B) which was carried out as many as 6 sessions obtained an average score of 53.8%. And the baseline phase 2 (A2) carried out as many as 3 sessions obtained an average score of 86%. The results of visual analysis in conditions show that the directional tendency increases from session to session, which means that it shows a change in good (+). Meanwhile, in the analysis between conditions, the level change from the baseline phase to the intervention phase increased from the previous data, while the percentage of overlap after calculating the intervention conditions to the baseline obtained an overlap percentage of 50%, which means that the intervention has a good effect. While in the intervention condition with baseline condition 2, an overlap percentage of 0% was obtained, which means that the intervention has a good effect on braille reading ability, the conclusion that can be drawn is that changes in braille reading ability in blind children occur due to braille reading interventions using the SAS method.